Поводження з фотоелектричними панелями об'єктів сонячної енергетики - Самойленко, Наталія Миколаївна; Катенін, Вадим Дмитрович (Національний університет "Львівська політехніка", 2021)
Solar energy usage trends in Ukraine and features of waste generation of photovoltaic panels are considered. Objective needs for the development of a precise system of waste management and end-of-life photovoltaic panels disposal technologies in the country are defined. The directions for an efficient photovoltaic panels waste management systems creation, which takes into account the forward-looking aspects of waste generation, are offered
Keywords: сонячна енергетика; відновлювальні джерела енергії; фотоелектричне обладнання; тонкоплівкові сонячні батареї; утилізація фотоелектричних модулів; переробка; забруднення довкілля; електронні відходи